Effects of the native-invasive-alien substitution of ecosystem engineers on sediment reworking and nutrient cycling - Lopes, Marta L.; Crespo, Daniel; Costa, Valentina; Rainha, Paulo; Sousa, Ana I.; Lillebø, Ana I. (Frontiers in Marine Science, 2025)
IntroductionRia de Aveiro, a coastal lagoon on the Atlantic coast of Portugal, was invaded by Arenicola spp. 15 years ago, with the new species successfully spreading throughout the system and replacing the native Diopatra species. With opposite bioturbation traits (Diopatra as sediment stabilizers vs Arenicola as sediment reworkers), the impacts of this replacement can spread across the entire ecosystem.MethodsIn a 21 days microcosm study, we evaluated the effects of the incremental substitution of Diopatra by Arenicola species on relevant proxies of ecosystem functioning, such as sediment reworking depths and nutrient dynamics.ResultsThe results show a strong directional influence on most of the analyzed parameters as a response to higher densities of Arenicola. Specifically, Arenicola-dominated communities were characterized by deeper reworking depths and higher concentrations of ammonium and phosphate in the water column.DiscussionThese results are discussed in the context of the available knowledge on the accompanying biological communities, which are typically fostered by these distinct functional groups. Therefore, there is strong evidence that the introduction of a novel species’ trait will have major consequences across several levels of the invaded system.